JURIDICAL ANALYSIS OF EFFORTS IN REGULATING THE PROTECTION AND MANAGEMENT OF CULTURAL HERITAGE IN PASER DISTRICT - Bagus Anwar Hidayatulloh; Cunduk Wasiati; Kelik Endro Suryono (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The Indonesian state has a constitutional obligation to advance national culture, as mandated by Article 32 paragraph (1) of the 1945 Constitution, which guarantees the freedom of the people to preserve and develop cultural values. Indonesian culture, reflecting the nation's noble values, must be embraced by all citizens to strengthen national identity, enhance dignity, and reinforce unity to achieve the nation's future aspirations. Historical objects, structures, and buildings are crucial to preserve to provide an understanding of current social and physical realities. In Paser Regency, rapid development has negatively impacted efforts to protect and preserve historical traditions and culture. Cultural heritage, such as Cultural Heritage Objects, Cultural Heritage Buildings, and others, have not been officially recognized as cultural heritage by the local government. The management of valuable historical traces has not been comprehensive, with current management more oriented towards tourism and religious activities. An academic draft of a Regional Regulation on the Protection, Preservation, and Management of Cultural Heritage is needed to optimize the management and preservation of cultural heritage in Paser Regency. This would enable the community to better understand history and support overall community empowerment.